The Role of Interpersonal Communication in Supporting Student Development through School Counseling - Handi, Esther Freya Angelica; Teguh, Monika (Future Science, 2025)
This study aims to deepen the understanding of effective interpersonal communication practices in school counseling settings and to contribute to the advancement of educational communication theory and practice in Indonesia. Employing a descriptive qualitative method, data were collected through in-depth interviews and document analysis involving guidance counselors at Karangturi High School, Semarang. The findings indicate that interpersonal communication between guidance counselors and students serves as a key determinant of counseling service effectiveness. Communication founded on trust, openness, and appreciation enables the development of supportive relationships that enhance students’ motivation and academic achievement. The application of core communication components—sender, message, channel, receiver, and feedback—was effectively adapted across both face-to-face and online interactions, particularly through platforms such as WhatsApp. Moreover, principles of interpersonal communication, including active listening, empathy, and positive reinforcement, were evident in counselors’ approaches, fostering students’ sense of value and belonging. The study also reveals that personal factors (counselors’ experience and personality) and situational factors (class size, stigma, time constraints, and Generation Z’s digital preferences) significantly influence communication effectiveness. Counselors’ adaptive use of digital communication and proactive engagement strategies demonstrate their responsiveness to the evolving dynamics of student interaction in the modern era. Overall, the study underscores that interpersonal communication is not merely a technical competency but a pedagogical and emotional strategy that underpins effective counseling, holistic student development, and the creation of a more inclusive and responsive educational environment.